Via(da)gens teológicas : itinerários para uma teologia queer no Brasil - Musskopf, André Sidnei (2008)
The main argument of this Dissertation is that theology needs to walk other paths. Although this calling is directed to all theologies which are based on a heterocentric matrix for the construction of theological knowledge, it is especially directed to Latin-American Liberation Theology, which the reflections of this Dissertation are understood to be in continuation with. The themes that it discusses were selected and organized based on the paths crossed by the author himself, which became itineraries at the same time crossed and suggested as necessary for the construction of a queer theology in Brazil. This way, the reflections are situated in two specific contexts that determinate its approach. First, concentrating the research on the Brazilian context, which becomes evident in the historical re-reading of the processes of construction of the discourses and practices around religiosity and sexuality in Brazil, as well as the Brazilian identity in a wider sense, and their importance for the theological reflection. Second, because it takes on the developments in the area of queer theology as a privileged space of dialog, which becomes evident in the presentation of the emergence and development of homosexual-gay-queer theologies since the XIX century and, especially, during the second half of the XX century, mainly in English speaking countries, but also in Brazil and Latin America, even if in less formal spaces usually made invisible spaces. From those two specific contexts emerges the questioning of traditional theological epistemologies and the challenge of articulating ambiguity as an epistemological principle. Such ambiguity is, then, discussed conceptually from the studies in several areas and by several authors and defined from the contexts where the need for its articulation emerged: the Brazilian context and queer theory. Its strongest articulation, however, is developed in three narratives presented as "sexual stories" that start the reflexive process about theological epistemology. This reflection is organized in three moments "occupy, resist, produce" one of the most well known slogans of the Landless Workers Movement (MST). From then on the discussion turns into a conversation between the "sexual stories" and several authors who have worked on the epistemological debate, considering issues of identity and language in the intersection with the discussions on gender, sexuality, race/ethnicity, class and ecology. Although the three moments of this epistemological proposal developed from the idea of ambiguity are part of the same movement of knowledge production, in the last one the proposals for the construction of a queer theology in Brazil are materialized through the dialog with Frida Kahlo s painting "La venadita". The character which marks and names the painting a deer and its association with homosexuality in the Brazilian context, through a process of symbolic appropriation and in accordance with the discussion accomplished in the previous chapters, allow the definition of those reflections as via(da)gens teológicas [theological faggoting] giving concrete expression to the itineraries for a queer theology in Brazil.